2016
DOI: 10.1111/ajgw.12238
|View full text |Cite
|
Sign up to set email alerts
|

New multipest damage indicator to assess protection strategies in grapevine cropping systems

Abstract: Background and Aims Social, environmental and regulatory evolution encourages grapegrowers to reduce chemical use. Organic production is one possible answer, but controlling pests and diseases by products allowed in organic production is less easy than with chemicals. We integrated disease severity levels (Botrytis bunch rot, powdery and downy mildews) and pest incidence (grape berry moths) to develop an indicator of pests and disease damage in grape bunches, named assessment indicator of damage in grape bunch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…A significant drop in per-hectare yields in organic farming compared to conventional agriculture has been observed (de Ponti et al 2012;Seufert et al 2012), but related economic losses have not been demonstrated. For grapevines, the risk of yield losses seems to be important during organic conversion because grape yields are highly sensitive to pests and diseases (Fermaud et al 2016). Organic farming labor requirements and total costs per hectare can be two or three times greater than those in conventional agriculture (Aubert and Enjolras 2017) depending on cropping choices (e.g., mechanization) and pre-conversion synthetic chemical dependency.…”
Section: Introductionmentioning
confidence: 99%
“…A significant drop in per-hectare yields in organic farming compared to conventional agriculture has been observed (de Ponti et al 2012;Seufert et al 2012), but related economic losses have not been demonstrated. For grapevines, the risk of yield losses seems to be important during organic conversion because grape yields are highly sensitive to pests and diseases (Fermaud et al 2016). Organic farming labor requirements and total costs per hectare can be two or three times greater than those in conventional agriculture (Aubert and Enjolras 2017) depending on cropping choices (e.g., mechanization) and pre-conversion synthetic chemical dependency.…”
Section: Introductionmentioning
confidence: 99%
“…These high figures are due to vineyards being extremely sensitive to attacks from pests and diseases such as powdery and downy mildew [7,8]. If not controlled, powdery and downy mildew expose winegrowers to a risk of low to null harvest [9]. In light of this environmental context and rising consumer demand, organic vineyard areas have increased since 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Water or nitrogen stresses are essential limiting factors of yield that constrain the number of inflorescences and the number of berries at the sensitive period [13]. Delayed bud pruning can result in poor vine canopy management, which can then lead to a degraded microclimate around clusters and higher disease severity [9]. For pest and disease control, alternative products based on copper, sulfur or biocontrol exist.…”
Section: Introductionmentioning
confidence: 99%
“…During conversion, farmers must stop using synthetic chemicals and mineral fertilization to comply with organic farming certification requirements. Substituting inputs allowed in organic farming (e.g., copper instead of systemic fungicides) for synthetics may be considered a minor change but in practice requires significant changes in crop management to avoid declines in yield and/or grape quality (Fermaud et al 2016). In vineyards, major outbreaks of certain diseases can stem from just one poor application of fungicide and result in a near total yield loss (Caffi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The technical and biophysical subsystems are influenced by the decisional subsystem, which comprises decision rules for crop land allocation, crop combinations (in space and time), and crop management (Le Gal et al 2010). These decision rules are activated by management indicators (Fermaud et al 2016).…”
Section: Introductionmentioning
confidence: 99%